Stable human regulatory T cells switch to glycolysis following TNF receptor 2 costimulation - de Kivit, Sander; Mensink, Mark; Hoekstra, Anna T.; Berlin, Ilana; Derks, Rico J. E.; Both, Demi; Aslam, Muhammad A.; Amsen, Derk; Berkers, Celia R.; Borst, Jannie (Nature metabolism, 2020)
Following activation, conventional T (T conv ) cells undergo an mTOR-driven glycolytic switch. Regulatory T (T reg ) cells reportedly repress the mTOR pathway and avoid glycolysis. However, here we demonstrate that human thymus-derived T reg (tT reg ) cells can become glycolytic in response to tumour necrosis factor receptor 2 (TNFR2) costimulation. This costimulus increases proliferation and induces a glycolytic switch in CD3-activated tT reg cells, but not in T conv cells. Glycolysis in CD3–TNFR2-activated tT reg cells is driven by PI3-kinase–mTOR signalling and supports tT reg cell identity and suppressive function. In contrast to glycolytic T conv cells, glycolytic tT reg cells do not show net lactate secretion and shuttle glucose-derived carbon into the tricarboxylic acid cycle. Ex vivo characterization of blood-derived TNFR2 hi CD4 + CD25 hi CD127 lo effector T cells, which were FOXP3 + IKZF2 + , revealed an increase in glucose consumption and intracellular lactate levels, thus identifying them as glycolytic tT reg cells. Our study links TNFR2 costimulation in human tT reg cells to metabolic remodelling, providing an additional avenue for drug targeting. After activation, conventional T cells undergo metabolic reprogramming. de Kivit et al. show that in human thymic regulatory T cells, TNFR2 stimulation promotes a glycolytic switch with a preferential glucose-derived carbon flux into the TCA cycle to support suppressive functions.